Actions for the technical top setback spin in athletes of tennis of table - Omar Fernández Pérez; Tania Rosa García Hernández; Maidelín Díaz Miranda (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2020)
The work that sample the results of a study carried out in the development of the championships national school 2017 and 2018 is presented where the athletes of Tennis of Table of the category sub 13 years of the Eide of Pinar del Río they presented difficulties in the effectiveness during the made parties. With the result that in the search competitive achievements you outlines as objective for that investigation to improve the technical top setback spin in the school athletes of the Eide of Pinegrove of the River, assisting to the current tendencies of the sport training. Such scientific methods were applied as the observations, the interview, as well as they revised it different bibliographical sources that facilitated to diagnose the phenomenon to study and their possible solution with a system of actions strategic altars of solving the deficiencies that it exists in the athletes of tennis of table of the county of Pinar del Río.